The Great Exchange Rate Debate after Argentina - Sebastian Edwards (Oesterreichische Nationalbank (OeNB), 2002)
In this paper I discuss in what way, if any, the collapse of Argentina's experience with a currency board has affected the policy debate on the appropriate exchange rate regime in emerging and transition countries. More specifically, I deal with three issues: (1) I discuss some important aspects of the Argentine experience. (2) I provide a comparative evaluation of economic performance under strict dollarization. And (3), I analyze emerging countries' experiences with flexible exchange rates, including the issue of a fear of floating.
Keywords: 330